Feasibility of the City-driven Neutral Host Operator: The case of Helsinki - Jaume Benseny; Jaspreet Walia; Benjamin Finley; Heikki Hämmäinen (International Telecommunications Society (ITS), 2019)
The large-scale deployment of 5G small cells in an urban environment can be facilitated by allowing the placement of antennas on light poles and by organizing their commercial exploitation via a neutral operator. In this paper, we analyze the feasibility of a city-driven Neutral Host Operator (NHO) for the case of the Helsinki Metropolitan Area by comparing the costs of two alternative small cell deployment strategies. We estimate 5G deployment needs at the postal code level for three future demand scenarios considering different data consumption volumes as well as number of subscriptions for connected devices. For this, we add postal code capacity in a year basis updating existing macrocell sites to 5G and deploying new 5G macro/small cell sites depending on indoor/outdoor demand and offloading. By 2030, about 85%, 90%, and 92% of existing 4G macro sites need to be updated with 5G. Additionally, 34, 816, and 1035 outdoor small cells will be required to serve the three demand growth scenarios, respectively. Although the NHO-driven deployment strategy initially incurs higher costs than the MNO-driven, before 2030 the former accumulateslower costs for all demand scenarios. In case the NHO-driven strategy achieves a 20% cost-savings in public works, this strategy becomes costadvantageous in 2029 with 728 and 921 deployed small cells for the medium and high growth scenarios, respectively. Cost-saving mechanisms in the NHO-driven strategy should focus on public works since they are the largest contributor to the deployment cost.
Keywords: 330